The Influence of Knowledge Management and Soft Skills Development on Employee Perfomance in Public Works Agency - Berlian, Icahaya; Mardiana, Nova; Firdaus, Luthfi (LPPPIPublishing, 2025)
This study examines the influence of knowledge management and soft skills development on employee performance within the Public Works Agency in Indonesia. In today’s globalized and technologically advanced environment, employee performance is critical for organizational success. The research highlights that performance is no longer determined solely by technical abilities but also by the effective management of knowledge and the development of interpersonal competencies. Using a quantitative research design, data were collected from 215 respondents through a structured questionnaire and analyzed using multiple linear regression. The findings reveal that both knowledge management and soft skills development have a positive and significant effect on employee performance. Knowledge management through technology, procedures, and personal knowledge enables employees to access information efficiently and make informed decisions, thereby enhancing productivity. Similarly, soft skills such as communication, teamwork, ethical responsibility, and leadership are shown to improve collaboration and adaptability in the workplace. The statistical analysis, including t-tests, supports both hypotheses, indicating strong correlations between the independent variables and performance outcomes. The study concludes that effective knowledge management systems and soft skills training contribute substantially to achieving organizational goals.